2000
DOI: 10.1107/s0108270199014080
|View full text |Cite
|
Sign up to set email alerts
|

Sodium diphenylacetate, an infinite columnar structure

Abstract: In the title compound, Na+·C14H11O2−, the di­phenyl­acetate ions have a conformation where the two phenyl rings and the carboxyl­ate group are oriented like the blades of a propeller, each ion having a well defined helicity. The crystal structure of the title compound is achiral, although non‐centrosymmetric (space group ); thus, ions with both (+) and (−) helicities are present in the crystal. Each Na+ ion is coordinated by four carboxyl­ate O atoms at distances in the range 2.207 (2)–2.467 (3) Å to form cube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Ohta et al have shown that sodium diphenylacetate is one of this rare liquid crystals showing a hexagonal columnar mesophase [1]. The arrangement of the molecules in the liquid crystal phase correlates with and resembles that observed in the solid state, according to our study [2]. In the crystal structure of sodium diphenylacetate, each Na + ion is coordinated by four carboxylate O atoms at distances in the range 2.207 (2)-2.467 (3) Å to form cubes of Na and O atoms which are linked via the carboxylate C atoms into a columnar structure.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Ohta et al have shown that sodium diphenylacetate is one of this rare liquid crystals showing a hexagonal columnar mesophase [1]. The arrangement of the molecules in the liquid crystal phase correlates with and resembles that observed in the solid state, according to our study [2]. In the crystal structure of sodium diphenylacetate, each Na + ion is coordinated by four carboxylate O atoms at distances in the range 2.207 (2)-2.467 (3) Å to form cubes of Na and O atoms which are linked via the carboxylate C atoms into a columnar structure.…”
Section: Introductionsupporting
confidence: 87%
“…Refinements were carried out with SHELXL-97 [6] package. All refinements were made by full-matrix least-squares on F [2], with anisotropic displacement parameters for all nonhydrogen atoms. Hydrogen atoms were included in the refinement in calculated positions.…”
Section: Preparation Of Diphenylacetic Acidmentioning
confidence: 99%
“…In 2000, we have elucidated the structure of a crystalline phase of sodium diphenylacetate showing that the ions and cations are aggregated in columns [2]. In such structure, the diphenylacetate ions have a conformation where the two phenyl rings and the carboxylate group are oriented like the blades of a propeller, each ion having a well-defined helicity Each Na ?…”
Section: Introductionmentioning
confidence: 99%